2020
DOI: 10.3390/microorganisms8071033
|View full text |Cite
|
Sign up to set email alerts
|

Current Evidence on the Ocular Surface Microbiota and Related Diseases

Abstract: The ocular surface microbiota refers to the resident non-pathogenic microorganisms that colonize conjunctiva and cornea. Several studies have shown that ocular surface epithelial cells can respond selectively to specific components of ocular pathogenic bacteria by producing pro-inflammatory cytokines and, in contrast, they do not respond to non-pathogenic bacteria, thus supporting the colonization by a real microbiota. However, the analysis of the ocular microbiome composition is essential for understanding th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
71
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(77 citation statements)
references
References 75 publications
3
71
1
2
Order By: Relevance
“…Corynebacterium species can be found commonly on the ocular surface, in conjunction with other indigenous bacteria, such as Staphylococcus epidermidis and Propionibacterium acnes [ 1 , 5 ]. These various commensal bacteria aid in preventing ocular surface from invasion by foreign organisms [ 6 ]. However, in immunocompromised patients, many recent reports have demonstrated that Corynebacterium species can be potentially pathogenic when present on the ocular surface [ 7 , 8 , 9 , 10 ], as this infection has been associated with cases of endocarditis of the aortic and mitral valves [ 11 ], granulomatous mastitis [ 12 ], and pelvic osteomyelitis [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Corynebacterium species can be found commonly on the ocular surface, in conjunction with other indigenous bacteria, such as Staphylococcus epidermidis and Propionibacterium acnes [ 1 , 5 ]. These various commensal bacteria aid in preventing ocular surface from invasion by foreign organisms [ 6 ]. However, in immunocompromised patients, many recent reports have demonstrated that Corynebacterium species can be potentially pathogenic when present on the ocular surface [ 7 , 8 , 9 , 10 ], as this infection has been associated with cases of endocarditis of the aortic and mitral valves [ 11 ], granulomatous mastitis [ 12 ], and pelvic osteomyelitis [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, the surface of the eye is directly exposed to the external environment and hence is susceptible to airborne microbial contamination frompotentially pathogenic microbes including viruses, bacteria, fungi and parasites and their pathogen-associated molecules.Airborne contamination includes SARS-CoV-2, often as an aerosolized spray ofmicro-droplets, and isthe major known form of a highly infectiveSARS-CoV-2viral transmission [24,51,53,56].Besides different protective anti-microbial substances in the tear uid such as mucins andglobular glycoproteins such as lactoferrin, the tear mucosal lm which coats the cornea and conjunctiva contains multiple anti-microbial components including lysozyme (also known as muramidase or N-acetylmuramide glycan-hydrolase), cationic antimicrobial peptides, surfactant protein-D, several RNAse enzymes,S100A peptidessuch as psoriasin (S100A7) and others, and these are important components of the innate-immune defense system of the eye providing protection against a wide range of potential airborne ocular pathogens [57,58; unpublished observations]. Interestingly, there is recent evidence that the ocular surface microbiota, the resident nonpathogenic symbiotic microorganisms that colonize the conjunctiva and cornea, and the microbiota of other areas of the body, such as the gastrointestinal (GI) tract and oral microbiome are involved in the development and pathophysiology of several ophthalmic diseases including the susceptibility to microbial, and in particular, viral transmission and infection [49][50][51][52][53]59]. Of further emerging interest are the effects of SARS-CoV2 invasion on the biochemistry, molecular genetics and innate-immunity of neural and ocular host cells and the viral-mediated induction of post-transcriptional and pro-in ammatory signaling factors including certain microRNAs (miRNAs) that modulate the expression of genes involved in viral replication, neuro-in ammation, innate-immune signaling and progressive and age-related aspects of in ammatory neurodegeneration [50][51][52][53]59].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is reported that long-term use of prostaglandin analogs may alter conjunctival microbial flora [20]. The alteration of the normal flora can cause inflammation, delayed healing and susceptibility to pathogen invasion, followed by worsening of ocular surface diseases [1]. Approximately 49-59% of patients with glaucoma experience ocular surface diseases related to the use of glaucoma eyedrops but these problems have been under-recognized and under-treated to allow for better control of IOP.…”
Section: Discussionmentioning
confidence: 99%
“…Blinking, tear film, microbial commensal, ocular immunity and epithelial barrier are necessary to maintain the homeostasis and health of ocular surface. However, these defense mechanisms may be compromised in various diseases, leading to the severe discomfort and even visual impairment [1].…”
Section: Introductionmentioning
confidence: 99%